2009
DOI: 10.1007/s00216-009-3201-2
|View full text |Cite
|
Sign up to set email alerts
|

Analytical characterization of polymers used in conservation and restoration by ATR-FTIR spectroscopy

Abstract: In the last few decades many new polymers have been synthesized that are now being used in cultural heritage conservation. The physical and chemical properties and the long-term behaviors of these new polymers are determined by the chemical composition of the starting materials used in their synthesis along with the nature of the substances added to facilitate their production. The practical applications of these polymers depend on their composition and form (foam, film, sheets, pressure-sensitive adhesives, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(81 citation statements)
references
References 19 publications
7
55
0
Order By: Relevance
“…Figure 4 shows an example of a fragment identified as polypropylene, due to intense absorption peaks between 3000 and 2800 cm −1 (CH stretching region), at 2845 (ν CH), 1458 (δ CH 2 ), and 1377 (δ CH 3 ) cm −1 (Andreassen 1999; Asensio et al 2009; Verleye et al 2001; Noda et al 2007; Jung et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows an example of a fragment identified as polypropylene, due to intense absorption peaks between 3000 and 2800 cm −1 (CH stretching region), at 2845 (ν CH), 1458 (δ CH 2 ), and 1377 (δ CH 3 ) cm −1 (Andreassen 1999; Asensio et al 2009; Verleye et al 2001; Noda et al 2007; Jung et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…6. The spectra collected on the fibre show absorptions at 3024 (aromatic C–H stretching vibrations), 2908 and 2847 (CH 2 stretching), 1949 and 1878 (combination bands), 1600 and 1492 (aromatic ring stretching), and 1446 (CH 2 bending) and 1018 (aromatic CH bending) cm −1 which are characteristic of polystyrene (Verleye et al 2001; Noda et al 2007; Asensio et al 2009; Biazar et al 2010; Olmos et al 2014; Jung et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the MPs polymers found polystyrene n=40 (PS, 67%) and polyvinyl chloride n=20 (PVC, 33%) of MPs particles in the beach sediment. The absorption bands of these polymers have been recognized by direct matching within the wave-numbers of the absorption bands, as we discussed in the methodology section with the reference spectra of [5,31,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of pristine LDPE is characterized by bands ( Figure 7, curve a) associated with -CH 2 -stretching (2848 and 2915 cm -1 ), asymmetric C-H and -CH 3 bending in plane (1460 and 1470 cm -1 , respectively), symmetric C-H bending in plane (1377 cm -1 ), and C-H (-CH 2 -) n*6 rocking (doublet with maxima at 720 and 731 cm -1 ) [27]. The plasma surface treatment of LDPE resulted in significant spectral changes (Figure 7, curve+b), which provided clear evidence of the incorporation of certain oxygencontaining groups, i.e., -OH (region 3700-3080 cm -1 ) and/or other oxygen-containing products at the surface of the polymer (region 1845-1510, 1280, 1126, 1150 cm -1 , acid, ketone, aldehyde) [28].…”
Section: Surface Chemistry Analysismentioning
confidence: 99%